Pre-plasma effect on laser beam energy transfer to a dense target under conditions relevant to shock ignition. (30th March 2015) - Pisarczyk, T.; Gus'kov, S.Yu.; Renner, O.; Demchenko, N.N.; Kalinowska, Z.; Chodukowski, T.; Rosinski, M.; Parys, P.; Smid, M.; Dostal, J.; Badziak, J.; Batani, D.; et al.
Abstract This paper reports on properties of a plasma formed by sequential action of two laser beams on a flat target, simulating the conditions of shock-ignited inertial confinement fusion target exposure. The experiments were performed using planar targets consisting of a massive copper (Cu) plate coated with a thin plastic (CH) layer, which was irradiated by the 1ω PALS laser beam (λ = 1.315 μm) at the energy of 250 J. The intensity of the fixed-energy laser beam was scaled by varying the focal spot radius. To imitate shock ignition conditions, the lower-intensity auxiliary 1ω beam created CH-pre-plasma which was irradiated by the main beam with a delay of 1.2 ns, thus generating a shock wave in the massive part of the target. To study the parameters of the plasma treated by the two-beam irradiation of the targets, a set of various diagnostics was applied, namely: (i) Two-channel polaro-interferometric system irradiated by the femtosecond laser (~40 fs), (ii) spectroscopic measurements in the X-ray range, (iii) two-dimensional (2D)-resolved imaging of the Kα line emission from Cu, (iv) measurements of the ion emission by means of ion collectors, and (v) measurements of the volume of craters produced in a massive target providing information on the efficiency of the laser energy transfer to the shock wave. The 2D numerical simulations have been used to support the interpretation of experimental data. The general conclusion is that the fraction of the main laser beam energy deposited into the massive copper at two-beam irradiation decreases in comparison with the case of pre-plasma. The reason is that the pre-formed and expanding plasma deteriorates the efficiency of the energy transfer from the main laser pulse to a solid part of the targets by means of the fast electrons and the wave of an electron thermal conductivity.